Audit of admission to medical school: I–Acceptances and rejects. Issue 6453 (3rd November 1984) - McManus, I C; Richards, P
Abstract : A prospective study of the process of application, selection, and admission to medical school was performed. St Mary's Hospital Medical School received 1478 UCCA applications for admission in October 1981: 94 (6.4%) applicants entered St Mary's in October 1981, 436 (29.5%) entered other medical schools, 176 (11.9%) read a subject other than medicine, and 772 (52.2%) did not enter university. The study included 12.6% of all applicants and 12.9% of all entrants to British medical schools in October 1981. Educational qualifications, demographic variables, type of schooling, family background, and the manner of application were examined in relation to overall selection. A level achievement was the major determinant of acceptance. O level achievement, early application, and medical parents had significant but smaller independent effects on the chance of acceptance. Social class, age, sex, and school type did not predict acceptance when corrected for academic and other factors. Few differences in personality, career preference, cultural interests or attitudes were found between those accepted and those rejected.